Kemampuan Murid SMP Negeri 10 Pekanbaru Kelas VII Dalam Membaca dan Menulis Materi Dasar Arab Melayu - Hasnah Faizah; Aulia Putri Novia; Fatranita Putri Asyilla Suci (Universitas Muhammadiyah Enrekang, 2022)
This study aims to determine and describe the ability to read and understand Arabic-Malay writing at the SMP Negeri 10 level in class VII. The method used in this study is a descriptive method with a sample of 30 Class VII students at SMP Negeri 10 Pekanbaru 2022/2023. This sampling is known as a full sample or 100% of the total research population. The data collection technique used in this study was an objective test technique (multiple choice questions). Data analysis techniques by collecting test results, giving an assessment according to the score obtained, looking for the percentage of each aspect of students' reading comprehension of Malay Arabic writing, and finding/calculating the average value of all. This research is motivated by the lack of interest of current students in learning Arabic Malay because it is possible that this is not taught by the teacher and also not honed in the students' personal abilities. The problem in this study is how the ability to read and understand Arabic-Malay writing in a student is lacking.